The signal axis GATA2-EDN1-AGT induced hypertension from obstructive sleep apnea-hypopnea syndrome with the clinical and animal study - Zhang, Li; Xu, Shaokun; Zhou, Ning; Shen, Juanqin; Huang, Jiaqing; Sun, Dongsheng (Cellular and Molecular Biology, 2022)
Hypertension occurred in 50% obstructive sleep apnea-hypopnea syndrome (OSAHS) patients meanwhile OSAHS occurred in 30% hypertension patients. The present study aimed to explore the molecular mechanism of GATA2-EDN1-AGT induced hypertension in the development of obstructive sleep apnea-hypopnea syndrome. OSAHS patients (56 cases: 36 cases of male, 20 cases of female, 42~60 years old) were divided into two groups (case group: patients with hypertension monitored by 24 h ambulatory blood pressure and polysomnography; control group: patients without hypertension). Wistar rats were used to establish the OSAHS model (narrow pharyngeal cavity). PaO2 and PaCO2 of patients and rats were measured by an automatic blood gas analyzer. The profile of total protein in the OSAHS group and normal group was evaluated. Protein-protein-interaction (PPI) was carried out to show all matter proteins related. The levels of EDN-1, AGTII and atrial natriuretic peptide (ANP) in blood samples of patients and rats were analyzed by enzyme-linked immunosorbent assay (ELISA). The expression of GATA2, EDN1, endothelin-converting enzyme 1 (ECE-1) and AGTⅡ was measured. The results showed that SaO2 and AHI were positively associated with systolic pressure (P<0.05) in OSAHS patients. There was no correlation among other indexes (P>0.05). It was also observed that GATA2 had a strong relationship with AGTⅡ and EDN1. The results of ELISA presented that the levels of EDN1, AGTⅡ and ANP in the OSAHS group of human and animal models were significantly increased (P<0.05). The results of immunochemistry showed that the expression of GATA2 and AGTⅡ in the vascular of OSAHS group was upregulated manifestly (P<0.05). It was concluded that OSAHS can induce AHI, which increases hypertension via the GATA2-EDN1-AGT Ⅱ axis.